Localization of 45S rDNA and telomeric sites on holocentric chromosomes of Rhynchospora tenuis Link (Cyperaceae) - André L.L. Vanzela; Angeles Cuadrado; Marcelo Guerra (Genetics and Molecular Biology, 2003)
Rhynchospora tenuis Link (Cyperaceae) is a weed widely distributed in Brazil that presents a small number of holocentric chromosomes (2n = 4) with some autopolyploid populations (2n = 8). The haploid number n = 2 is considered as a derivative of the base number x = 5. 45S rDNA probes and telomeric DNA were hybridized in both chromosome races of R. tenuis, looking for indications of chromosome fusions. The results showed that hybridization sites of the telomeric probe were restricted to end chromosome regions whereas rDNA sites were terminally located. The chromosome race with n = 4 exhibited a doubled number of sites, with similar size and location to the hybridized sequences, confirming its autopolyploid origin. Furthermore, the terminal location of the single 45S rDNA site in the 2n = 4 race suggested that disploid reduction in Rhynchospora, from n = 5 to n = 2, was followed by elimination or reorganization events, keeping the terminal distribution of these sites, as in an others species of the genus.